Reducing losses inflicted by insect pests on cashew, using weaver ants as a biological control agent - SINZOGAN, ANTONIO ALAIN KOFFI (My University, 2015)
1 In Benin cashew plantations, yields and nut quality are lost mainly as a result of insect pests. In the present study, we investigated the effectiveness of the African weaver ant Oecophylla longinoda as a biocontrol agent against Beninese cashew pests. 2 In a 2-year study, nut yield and quality were compared among: (i) trees with weaver ants O. longinoda; (ii) trees where weaver ants were sugar-fed; (iii) integrated pest management (IPM) trees with weaver ants combined with fruit fly bait spray; and (iv) control trees receiving no control measures. 3 All treatments with ants showed significantly higher yields than the control, with the IPM treatment leading to the highest yield. Compared with the control trees, the ants, ant sugar-fed and the IPM trees produced 78%, 122% and 151% more nuts, respectively. Nuts produced on control trees were of a higher quality on average because they were less damaged by thrips (probably because the fruit fly bait worked as a contact poison on thrips); this was also the case for the IPM treatment. In absolute numbers, however, trees in ant treatments produced more first-quality nuts. 4 To achieve a broader and effective control of both coreid bugs and thrips, a combination of weaver ants and supplementary compatible control measures is recommended.
Keywords: Biocontrol; cashew yield; nut quality; Oecophylla longinoda; pest damages.